A comparison of all-inside and inside-out meniscal repair in elite athletes - Borque, K. A.; Laughlin, M. S.; Webster, E.; Jones, M.; Pinheiro, V. H.; Williams, A. (The American Journal of Sports Medicine, 2023)
Background: The popularization of all-inside (AI) meniscal repair devices has led to a shift away from the historical gold standard of inside-out (IO) meniscal repair without comparative studies to support the change.